Sufism and the scriptures : metaphysics and sacred history in the thought of 'Abd al-Karim al-Jili /: metaphysics and sacred history in the thought of 'Abd al-Karim al-Jili. (2020) - Morrissey, Fitzroy, 1991-
No abstract available